"Do You Understand Why I Don't Share That?": Exploring Tellability Within Untellable Romantic Relationship Origin Tales. Issue 3 (27th May 2018) - Jackl, Jennifer A.
Abstract : The purposes of this study were to gain a clearer conceptualization of what makes romantic relationship origin (RRO) stories untellable, and how an untellable RRO tale impacts a narrator. In-depth interviews and open-coding revealed RRO stories are untellable if the narrative might generate negative judgement of the characters or relationship, and/or negative sanctions. Untellable RRO stories caused narrators to feel narrative exhaustion, lack of validation, limit identity construction and joy, and perpetuate silence. Untellable RRO stories also created a secret story world for narrators. These findings provide a deeper understanding of narrative tellability and how narrators "story around" untellable tales.